Consumer Perceptions of Data Privacy and Its Impact on Marketing - Prof. Manigandan; Nirmal Yadav (International Journal of Scientific Research in Science, Engineering and Technology, 2025)
This thesis explores the multifaceted relationship between consumer perceptions of data privacy and its implications for marketing strategies. In an increasingly datadriven world, consumers are becoming more aware of how their personal data is collected, used, and shared by businesses. This growing awareness influences their trust, engagement, and willingness to share information, directly impacting the effectiveness of various marketing efforts. This research aims to understand the current landscape of consumer privacy concerns, identify key factors shaping these perceptions, and analyze how these perceptions translate into behavioral responses towards marketing practices. The study will also provide actionable insights for marketers to build trust, ensure compliance with privacy regulations (e.g., DPDP Act, GDPR, CCPA), and develop ethical and effective marketing strategies in the age of data privacy.